Guaranteed Minimum Pensions - Conversion To Main Benefits - Pires, Patrícia Bárbara (2021)
In the defined benefits schemes in the United Kingdom (UK), the pension provided to the pensioners is divided in two components: Guaranteed Minimum Pension (GMP) and Excess. However, GMP is only a part of the accumulated benefit pension between 6th April 1978 and 5th April 1997 and it is treated way different from Excess. The way Guaranteed Minimum Pension is treated causes many inequalities between men and women, in particularly due to the differences on the GMP Payment Age and on the accrual rate. These inequalities felt by the members of the scheme led to a judgment in court, Lloyds case. This case allowed and established the use of some methods to equalize pensions. However, it is being considered other method due to the uncertainty about the GMP equalization, which was recently clarified. GMP "follows a journey" of four steps and the last step of the GMP Journey is the conversion of the GMP benefits in standard benefits. In consequence, the main goal of this work is to develop a generic calculation model of the conversion of that standard benefits, providing an easier treat and consideration in the calculations. Thus, the pension schemes will have minor data administration and actuarial calculations expenses. Also, it will become easier to communicate the information to the members of the scheme and to the State.